ATP sensitive K+ channels are critical for maintaining myocardial perfusion and high energy phosphates in the failing heart. (March 2016) - Jameel, Mohammad N.; Xiong, Qiang; Mansoor, Abdul; Bache, Robert J.; Zhang, Jianyi
Abstract: Congestive heart failure (CHF) is associated with intrinsic alterations of mitochondrial oxidative phosphorylation which lead to increased myocardial cytosolic free ADP. ATP sensitive K + channels (KATP ) act as metabolic sensors that are important for maintaining coronary blood flow (MBF) and in mediating the response of the myocardium to stress. Coronary adenosine receptors (AdR) are not normally active but cause vasodilation during myocardial ischemia. This study examined the myocardial energetic response to inhibition of KATP and AdR in CHF. CHF (as evidenced by LVEDP > 20 mm Hg) was produced in adult mongrel dogs (n = 12) by rapid ventricular pacing for 4 weeks. MBF was measured with radiolabeled microspheres during baseline (BL), AdR blockade with 8-phenyltheophylline (8-PT; 5 mg/kg iv), and KATP blockade with glibenclamide (GLB; 20 μg/kg/min ic). High energy phosphates were examined with 31 P magnetic resonance spectroscopy (MRS) while myocardial oxygenation was assessed from the deoxymyoglobin signal (Mb-δ) using 1 H MRS. During basal conditions the phosphocreatine (PCr)/ATP ratio (1.73 ± 0.15) was significantly lower than in previously studied normal dogs (2.42 ± 0.11) although Mb-δ was undetectable. 8-PT caused ≈ 21% increase in MBF with no change in PCr/ATP. GLB caused a 33 ± 0.1% decrease in MBF with a decrease in PCr/ATP from 1.65 ± 0.17 to 1.11 ± 0.11 (p < 0.0001). GLB did not change the pseudo-first-order rate constant of ATP production via CK ( k f ), but the ATP production rate via CK was reduced by 35 ± 0.08%; this was accompanied by an increase in Pi /PCr and appearance of a Mb-δ signal indicating tissue hypoxia. Thus, in the failing heart the balance between myocardial ATP demands and oxygen delivery is critically dependent on functioning KATP channels.